PEMBERDAYAAN LOKALITAS DAN KREATIVITAS: UPAYA MENUJU BANDUNG KOTA KREATIF - Tri Rahayu; Roni Sugiarto (ATRIUM: Jurnal Arsitektur, 2016)
Title: Empowerment of Locality and Creativity: The Effect towards Bandung Creative City As modernity with all rigidity and practically increasingly creeping, the locality was still elegant with its charm. Localities seems to be a special allure which become healer of longing of the past. Everything related to tradition inspires architects and city planners. Creative design certainly has allure for residents, local and non local tourists. Bandung is the city wellknown as Paris Van Java, which has consequence to the arrangement of the infrastucture and face of the city with strong identity of exquisite Sundanese culture. These opportunities would require creativity which offer uniqueness and special identity of Bandung. The study of city arrangement, planning stategy towards creative city, and sustainable strategy would be essential to realize the Bandung Creative City. The study was conducted by observing Bandung infrastucture at some central points in the heritage building until face of the city, and how the goverment‘s strategy to overcome this problem, related to creativity. The result shows that efforts to Bandung Creative City is done through empowerment of ?creative economy‘ in fashion, culinary, and design decorate city faces up to hilly region. Creative city allows the achivement of community prosperity and economically independence. Furthermore, through ?Bandung Creative City‘ program, the impact is not only to the creative city but also to a ‘smart city‘ which is done the following strategies: innovation, decentralization, and collaboration.